Tail‐Cuff Technique and Its Influence on Central Blood Pressure in the Mouse. Issue 6 (June 2017) - Wilde, Elena; Aubdool, Aisah A.; Thakore, Pratish; Baldissera, Lineu; Alawi, Khadija M.; Keeble, Julie; Nandi, Manasi; Brain, Susan D.
Abstract : Background: Reliable measurement of blood pressure in conscious mice is essential in cardiovascular research. Telemetry, the "gold‐standard" technique, is invasive and expensive and therefore tail‐cuff, a noninvasive alternative, is widely used. However, tail‐cuff requires handling and restraint during measurement, which may cause stress affecting blood pressure and undermining reliability of the results. Methods and Results: C57Bl/6J mice were implanted with radio‐telemetry probes to investigate the effects of the steps of the tail‐cuff technique on central blood pressure, heart rate, and temperature. This included comparison of handling techniques, operator's sex, habituation, and influence of hypertension induced by angiotensin II. Direct comparison of measurements obtained by telemetry and tail‐cuff were made in the same mouse. The results revealed significant increases in central blood pressure, heart rate, and core body temperature from baseline following handling interventions without significant difference among the different handling technique, habituation, or sex of the investigator. Restraint induced the largest and sustained increase in cardiovascular parameters and temperature. The tail‐cuff readings significantly underestimated those from simultaneous telemetry recordings; however, "nonsimultaneous" telemetry, obtained in undisturbed mice, were similar to tail‐cuff readings obtained in undisturbed mice on the same day. Conclusions: This study reveals that the tail‐cuff technique underestimates the core blood pressure changes that occur simultaneously during the restraint and measurement phases. However, the measurements between the 2 techniques are similar when tail‐cuff readings are compared with telemetry readings in the nondisturbed mice. The differences between the simultaneous recordings by the 2 techniques should be recognized by researchers.